Prevalence and Determinants of Drug Adherence in Type 2 Diabetes Mellitus Patients - Mendrofa, Tuho Konsultasi; Girsang, Ermi; Nasution, Sri Lestari Ramadhani; Ginting, Chrismis Novalinda (Universitas Aisyah Pringsewu, 2022)
Compliance with type 2 patients with DM in taking medication is an important key in maintaining blood glycemic levels and preventing complications. This study was conducted to determine the prevalence and to investigate the determinants of medication adherence in type 2 patients with DM. A total of 250 types 2 patients with DM who visited Pulau Tello Health Center, South Nias Regency, were involved in this cross-sectional study. Collecting data using questionnaires and patient medical records. The results showed that the motivational variables (p= less than 0.001; PR= 2; 95%CI 1.560-2.668), family support (p= less than 0.001; PR = 4.2; 95%CI 2.827-6.496), individual coping (p = less than 0.001; PR=1.9; 95%CI 1.409-2.267), and income (p= less than 0.001; PR=1.7; 95%CI 1.346-2.258) were associated with medication adherence in type 2 patients with DM. family is the dominant variable that influences medication adherence in type 2 patients with DM. Patients with DM who does not adhere to medication are 7.8 times more likely to have poor support than patients who adhere to medication.Abstrak: Kepatuhan pasien DM tipe 2 dalam mengonsumsi obat menjadi kunci penting dalam menjaga glikemik darah dan pencegahan komplikasi. Studi ini dilakukan untuk mengetahui prevalensi dan menyelidiki determinan kepatuhan minum obat pada pasien DM tipe 2. Sebanyak 250 orang pasien DM tipe 2 yang berkunjung di Puskesmas Pulau Tello, Kabupaten Nias Selatan dilibatkan dalam studi cross-sectional ini. Pengumpulan data menggunakan kuesioner dan rekam medis pasien. Hasil penelitian menunjukkan bahwa variable motivasi (p= kurang dari 0,001; PR= 2; 95%CI 1,560-2,668), dukungan keluarga (p= kurang dari 0,001;PR = 4,2; 95%CI 2,827-6,496), koping individu (p= kurang dari 0,001; PR=1,9; 95%CI 1,409-2,267), dan pendapatan (p= kurang dari 0,001; PR= 1,7; 95%CI 1,346-2,258) berhubungan dengan kepatuhan minum obat pasien DM tipe 2. Dukungan keluarga merupakan variabel yang dominan berpengaruh terhadap kepatuhan minum obat pada pasien DM tipe 2. Pasien DM yang tidak patuh minum obat 7,8 kali kecenderungannya memiliki dukungan yang kurang baik dibanding dengan pasien yang patuh minum obat.